A cross sectional study on perceptions and promoting factors for eye donation among undergraduate medical students - Khatwani, Priyanka; Raghunath, Deepa; Sakalle, Salil (International Journal Of Community Medicine And Public Health, 2023)
Background: It is realized that voluntary corneal donation rate depends upon the level of awareness of various stakeholders in our society. the aim of the current study was to evaluate the characteristics that encourage eye donation among medical students. Methods: This study was carried out using a pretested self-administered questionnaire, in the month of February 2022 among 350 undergraduate medical students of a medical college in central India. After classes ended, authors delivered questionnaires to students in the classrooms, explaining the nature and aim of the study and requesting them to participate in the study. Results: 80% (280/350) of study subjects knew about eye donation. 54.8% (192/350) of study subjects were willing to donate their eyes. 89.1% knew that a big proportion of blindness is preventable. 98.6% of the study participants opined that vitamin A plays a significant role in preventing childhood blindness. three most important such factors as perceived by study participants were noble cause (44%, n=154), pleasure to support the blind people (36.3%, N=127) and inspiration from advertisement on TV by favorite actor (30%, N=105). 67.7% subjects said that blind religious beliefs are significant obstacle in eye donation. Conclusions: Majority of students support active participation in the dissemination of knowledge, lack of awareness is the primary impediment to cornea donation. The course curriculum should include both fundamental eye care and other preventive and promotive elements of corneal blindness.